O livro didático no contexto das políticas públicas educacionais - Furtado, Andréa Garcia (2010)
This thesis has as its object of study the textbook in the context of public educational policies. The evidence base is central to Law 9.394/96, of Directives and Bases of National Education, the National Textbook Program (Elementary Education - early years) and the National Invitation establishing the criteria to choose the textbook. Other research sources were consulted as references and analysis of historical and political context in which to insert the educational policies after LDB 9394/96. The research theme was theoretical: the concept of hegemony in Gramsci, the discussion on education from economic, social and cultural indicated by the authors Apple, Ferreira, Frigotto, Gentili, Ianni, Moraes and Saviani; empiricism that led the search process was the choice of textbooks from the viewpoint of the teacher, and from the standpoint of the administrative system. From the problem: which trends of educational policies that are articulated in the process of choosing a textbook in the post LDB/96? Goals have been formulated thus: to examine the educational policies in Basic Education - Elementary Education - Early Years in Law 9.394/96, of Directives and Bases of National Education, understand the politics of the textbook and identify trends in educational public policies in the process of choosing the textbook. To meet these goals, the chapters have been formulated to serve them. First, I present the "Methodological issues that underlie this debate," which proposed considerations relevant to the concept of hegemony by Gramsci proposed as the basis of theoretical support to reflect specifically on the policies of the National Program of Textbooks (NPDB) in the context of politics. The second chapter is on the "Contextualization of Brazilian politics," which highlights aspects of neoliberalism and education. The chapter on "Public Policy in Basic Education" presents the political-economic influences on the textbook, as well as existing relationships with the World Bank, with regard to education. The final chapter discusses "Trends in educational policy and its relation to the choice of textbooks." The final considerations indicate that the National Textbook Program intends to propose LDs quality, and the school, represented by the professionals who compose it, choose them within the limits set by law. By recognizing the power relations that surround the choice of LD, it is important to establish a teaching and administrative redirection so that you can think of an educational proposal that oportunize critical reflection of teacher and student; from these changes in attitude, it is expected involve the community in a posture of critical thinking focused on the promotion of man.